Plant thionins: structure, biological functions and potential use in biotechnology - T. I. Odintsova; M. P. Slezina; E. A. Istomina (Вавиловский журнал генетики и селекции)
Antimicrobial peptides (AMPs) are important components of defense system in both plants and animals. They represent an ancient mechanism of innate immunity providing rapid first line of defense against pathogens. Plant AMPs are classified into several families: thionins, defensins, nonspecific lipid-transfer proteins, hevein- and knottin-type peptides, hairpinins and macrocyclic peptides (cyclotides). The review focuses on the thionin family. Thionins comprise a plant-specific AMP family that consists of short (~5 kDA) cysteine-rich peptides containing 6 or 8 cysteine residues with antimicrobial and toxic properties. Based on similarity in amino acid sequences and the arrangement of disulphide bonds, five structural classes of thionins are discriminated. The three-dimensional structures of a number of thionins were determined. The amphipathic thionin molecule resembles the Greek letter Г, in which the long arm is formed by two antiparallel α-helices, while the short one, by two parallel β-strands. The residues responsible for the antimicrobial activity of thionins were identified. Thionins are synthesized as precursor proteins consisting of a signal peptide, the mature peptide region and the C-terminal prodomain. Thionins protect plants from pathogenic bacteria and fungi acting directly on the membranes of microorganisms at micromolar concentrations, although their precise mode of action remains unclear. In addition to plant pathogens, thionins inhibit growth of a number of human pathogens and opportunistic microorganisms, such as Candida spp., Saccharomyces cerevisiae, Fusarium solani, Staphylococcus aureus and Escherichia coli. Thionins are toxic to different types of cells including mammalian cancer cell lines. Transgenic plants expressing thionin genes display enhanced resistance to pathogens. A wide range of biological activities makes thionins promising candidates for practical application in agriculture and medicine.